1981
DOI: 10.1021/bi00509a032
|View full text |Cite
|
Sign up to set email alerts
|

Free energy changes in .alpha.-lactalbumin denaturation

Abstract: Previous work has shown that native alpha-lactalbumin (N) is completely denatured by the addition of guanidine hydrochloride (conformation D) but that partially denatured conformations appear in other denaturants. In particular, conformation I appears when the pH is lowered from 5.5 to 2.2 (I2.2) or when LiClO4 is added at pH 5.5 (I5.5). We have now determined the free energy changes for the processes N leads to I5.5, N leads to D5.5, and I2.2 leads to D2.2. We have also estimated the maximum value of the free… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
5
0

Year Published

1982
1982
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 9 publications
1
5
0
Order By: Relevance
“…ture, for D(LiC104)-RNase, are shown in Figure5. Both vary linearly with temperature (in the range of 4-64 °C) and exhibit no evidence of a conformational transition; similar ob-h i b i t e d .TableI: Comparison of the Conformational Behavior of D(LiC104)-RNase and D(pH)Ahmad & Bigelow (1979) and this paper for DfLiClO^-RNase andKuwajima et al (1976),Contaxis & Bigelow (1981),and Dolgikh et al (1981) for D(pH)-a-lactalbumin.…”
supporting
confidence: 59%
See 1 more Smart Citation
“…ture, for D(LiC104)-RNase, are shown in Figure5. Both vary linearly with temperature (in the range of 4-64 °C) and exhibit no evidence of a conformational transition; similar ob-h i b i t e d .TableI: Comparison of the Conformational Behavior of D(LiC104)-RNase and D(pH)Ahmad & Bigelow (1979) and this paper for DfLiClO^-RNase andKuwajima et al (1976),Contaxis & Bigelow (1981),and Dolgikh et al (1981) for D(pH)-a-lactalbumin.…”
supporting
confidence: 59%
“…Acetic acid greatly decreases the amplitude of the aromatic CD spectrum of tyrosine but affects the backbone CD spectrum of native RNase only slightly (Cann, 1971); this indicates that D(acetic acid)-RNase1 has some ordered backbone structure but disordered tyrosine side-chain conformations. Similarly, ordered structures have been observed for -lactalbumin denatured by lowering the pH [D(pH)-a-lactalbumin]1 (Kuwajima et al, 1976); the CD spectrum of the backbone was analyzed in terms of contributions from a helix, ß structure, and random coil, with the suggestion that D(pH)-a-lactalbumin appears to have a higher -helix but a lower /3-structure content than the native protein (Kuwajima, 1977;Contaxis & Bigelow, 1981). Neutral salts can act similarly to produce denatured proteins with some ordered structure (von Hippel & Schleich, 1969); many different kinds of neutral salts have been found to denature RNase (von Hippel & Wong, 1965; Ahmad & Bigelow, 1979), and the CD spectra of denatured RNase indicated that LiClG4 was the most effective in disordering the tyrosine side chains without inducing much change in the backbone structure.…”
mentioning
confidence: 97%
“…The first most convincing evidence for the presence of native-like residual structure in the heat denatured state of proteins came from Tanford and associates [ 19 ] who observed another cooperative transition between heat-denatured (X) state and GdmCl denatured (D) state on adding GdmCl to already heat-denatured proteins. (Latter many studies supported this observation (see, e.g., [ 8 , 20 , 21 , 22 ]).) All these studies led to the conclusion that the heat denatured state of proteins are less unfolded than the GdmCl-induced denatured state.…”
Section: Introductionmentioning
confidence: 87%
“…The primary structure of bovine a-Iactalbumin has been established (Brew et al, 1970). The conformation of this protein is pH-dependent (Kronman et al, 1965;Kuwajima, 1977;Contaxis & Bigelow, 1981). Bovine ao lactalbumin is resistant to in vitro proteolysis by pepsin at pH 6.0, which is the pH of calf abomasum contents immediately after feeding milk, but is degraded at pH 2.0 (Jenkins et al, 1980).…”
Section: Introductionmentioning
confidence: 99%